Influence of Al2O3 Addition on Structure and Mechanical Properties of Borosilicate Glasses - Bruns, Sebastian; Uesbeck, Tobias; Weil, Dominik; Möncke, Doris; van Wüllen, Leo; Durst, Karsten; de Ligny, Dominique (Frontiers in Materials, 2020)
Alkali-borosilicate glasses are one of the most used types of glasses with a high commercially and technological importance. In order to optimize glasses for diverse applications the understanding of the correlation between the microscopic structure and the macroscopic properties is of central interest in material sciences. It has been found that the fracture response of borosilicate glasses can be influenced by changes in the network interconnectivity. In the NBS2 borosilicate glass system (74.0SiO2-20.7B2O3-4.3Na2O-1.0Al2O3 in mol%), two subnetworks are present, i.e. a silicate and a borate network. Increasing cooling rates while processing were found to increase interconnectivity between the networks which in turn improves the glasses fracture response and is accompanied by an increasing capacity for densification. In the present study the borosilicate glasses were systematically modified by addition of up to 4.0 mol% Al2O3. Changes in the connectivity and short to medium-range order of the glass structure are characterized using Raman and NMR spectroscopic techniques. Both the Raman and the 11B NMR results show that as the Al2O3 content increases, a proportion of fourfold-coordinated boron are converted to threefold-coordinated ones. Additional 27Al NMR experiments show that aluminum is dominantly present in four-fold coordination. Aluminum-tetrahedra are thus charge balanced by sodium ions and incorporated into the silicate network. Finally, the inherent glass structure and its network interconnectivity is linked to the mechanical glass response. Nanoindentation testing, where shear flow, inelastic densification as well as cracking can be present, was employed for this purpose. It was found that the glass softens with increasing Al2O3 levels, which enhances the fracture response of the borosilicate glass.